Islamophobia Fallacies in the UK Press Headlines - Kamal Abdulmajeed, Rufaidah; Laith Yunis, Lina (Opción, 2019)
Violating one of the criteria of a good argumentative discourse leads to fallacious conclusions that consequently violate the truth of any proposition. The current study aims at proving the fallacies of Islamophobia that are known as the fear and hatred of Islam and Muslims and reflected on a number of headlines in UK press. As long as press and media are considered the only and the most reliable source of information for people round the world, some of UK press media have a fun- damental role in presenting a negative image of Islam and Muslims to the world. Language recently appears to be like weapons in the hand of journalists in order to attack Islam and Muslims starting a war of words towards them. The researchers follow Damer T.E. (2009) as their model to analyze the data by diagnosing the lexical signals that prove fallacy in these headlines. It is found that journalist have no good premises to convince people and prove their linguistic war to Islam and Muslims as being a source of danger and terrorism. They violate the criteria of their argumentative discourse by using false evidence which leads to false conclusion. Finally, it is recommended that the religion of Islam holds a message of love and peace that what is linguistically proved throughout the present study.